Post-Progression Survival after EGFR-TKI for Advanced Non-Small Cell Lung Cancer Harboring EGFR Mutations - Kogure, Yoshihito (PLoS One, 2015)
BACKGROUND: Non-small cell lung cancer (NSCLC) patients that harbor epidermal growth factor receptor (EGFR) mutations benefit from receiving an EGFR-tyrosine kinase inhibitor (TKI); however, post-progression survival (PPS) after EGFR-TKI treatment has not been sufficiently studied. METHODS: We retrospectively reviewed the clinical data from stage IV or recurrent NSCLC patients who harbored EGFR mutations and who received EGFR-TKI as their first-line treatment in our institute between 2009 and 2011. RESULTS: In total, 36 patients received EGFR-TKI treatment as their first-line therapy. Of those 36 patients, 30 experienced recurrence and were enrolled in this study. The median progression-free survival (PFS) of these patients was 8.2 months. Twelve patients received EGFR-TKI treatment beyond the diagnosis of progressive disease (PD), and 8 received second-line therapy. The PPS after EGFR-TKI treatment was 9.1 months, and survival after the termination of EGFR-TKI treatment in those patients treated with second-line chemotherapy was 13.9 months. The site of relapse was investigated and PFS in EGFR-TKI-treated patients with relapse in the brain (11.6 months) showed a trend toward a longer PFS compared with patients with relapse at other sites (8.2 months). The median PPS after EGFR-TKI treatment also showed the same trend in each group (12.9 and 9.2 months, respectively). CONCLUSIONS: The PPS after EGFR-TKI treatment failure was 9.1 months, while the survival of patients who underwent second-line chemotherapy after the termination of EGFR-TKI treatment was 13.9 months, comparable with the overall survival of EGFR mutation-negative patients, as previously reported. The prognosis of these NSCLC patients with EGFR mutations varied according to the sites of recurrence after first-line EGFR-TKI treatment. Of particular note was the prognosis of patients with brain metastases, which tended to be better than that of patients with metastases to other sites.